Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection and Presence of Anti–SARS-CoV-2 Antibodies Among University Student Dormitory Residents, September–November 2020. (31st July 2021) - Segaloff, Hannah E; Cole, Devlin; Rosenblum, Hannah G; Lee, Christine C; Morgan, Clint N; Remington, Patrick; Pitts, Collin; Kelly, Patrick; Baggott, Jake; Bateman, Allen; Somers, Tarah; Ruff, Jeanne; et al.
Abstract: Background: Multiple severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreaks occurred at universities during Fall 2020, but little is known about risk factors for campus-associated infections or immunity provided by anti–SARS-CoV-2 antibodies in young adults. Methods: We conducted surveys and serology tests among students living in dormitories in September and November to examine infection risk factors and antibody presence. Using campus weekly reverse-transcription polymerase chain reaction (RT-PCR) test results, the relationship between survey responses, SARS-CoV-2 antibodies, and infections was assessed. Results: Of 6136 students, 1197 completed the survey and 572 also completed serologic testing in September compared with 517 and 414 in November, respectively. Participation in fraternity or sorority events (adjusted risk ratio [aRR], 1.9 [95% confidence interval CI, 1.4–2.5]) and frequent alcohol consumption (aRR, 1.6 [95% CI, 1.2–2.2]) were associated with SARS-CoV-2 infection. Mask wearing during social events (aRR, 0.6 [95% CI, .6–1.0]) was associated with decreased risk. None of the 20 students with antibodies in September tested positive for SARS-CoV-2 during the semester, while 27.8% of students who tested RT-PCR positive tested negative for antibodies in November. Conclusions: Frequent drinking and attending social events were associated with SARS-CoV-2 infection. Antibody presence in September appeared to be protective from reinfection, but this finding was not statistically significant.